P-201 Supervision not snooper vision: a whole system approach to clinical supervision. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Firth, Pam; Curry, Tanya; Burton, Beth
Abstract : Aims: Staff working in hospice and palliative care need to be valued, given support and work to high standards. Good supervision acts as a protector against "burn out", builds a resilient work force and is a requirement for registration of some professional bodies. The nursing and midwifery councilMarch 2015 stated; "Clinical Supervision is an activity that brings skilled supervisors and practitioners together in order to reflect upon their practice" Anecdotal evidence suggests that supervision initiatives eventually fail, particularly if the hospice leadership changes. The CEO and clinical leaders at the hospice were determined to set up a top down service and employed a consultant to assess the need and deliver a programme of teaching and learning that could be sustained. Method: Assessment showed some senior members of the multi professional team received excellent external supervision. Amodel of group supervision for those not included would be developed for clinical staff. Subsequently an amended model would be used for staff and volunteers e.g. fundraisers and retail staff. Recommendation was to use a whole system approach and identify staff willing to train and become internal supervisors. A two day training programmewhich included contracting, boundaries, confidentiality, reflection and group work theorywas devised and delivered to 20 perspective supervisors. They received a half a day update and regular debriefs. All staff were trained in the use and expectations of supervision. Day course organised for fundraisers etc. Supervision model: The model adopted was to promote empowerment, learning, build confidence and self-esteem, growth and support. Individual self-reflection, awareness and the quality of care was prioritised. Review and evaluation: Review after 3 sessions. Evaluation after 1 year.